Pengaruh Reksa Dana Syariah, Saham Syariah dan Sukuk terhadap Pertumbuhan Ekonomi di Indonesia Dengan Inflasi Sebagai Variabel Moderasi - Safitri, Inchi; Mustakim Muchlis; Idris Parakkasi; Kamaruddin, Kamaruddin (Al-Buhuts, 2024)
This study aims to determine the effect of Islamic mutual funds, Islamic stocks and sukuk on economic growth in Indonesia with inflation as a moderating variable. This research uses a quantitative approach. The data source in this research is secondary data. The data analysis technique used in this research is Structural Equation Model (SEM) with Partial Least Square (PLS) approach. The findings in this study indicate that Islamic mutual funds have a positive and insignificant effect on economic growth. Islamic stocks have a significant positive effect on economic growth. Sukuk has a negative and insignificant effect on economic growth. Inflation strengthens the relationship between Islamic mutual funds and economic growth and has a significant effect. Inflation weakens the relationship between Islamic stocks and economic growth and has a significant effect. Inflation weakens the relationship between sukuk to economic growth and has a significant effect. Inflation has a positive and significant effect on economic growth.